ANALISIS JALUR FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI TINGKAT ADOPSI TEKNOLOGI KONSERVASI LAHAN KERING DI KABUPATEN BANTUL PROPINSI DAERAH ISTIMEWA YOGYAKARTA - R Kunto Adi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2005)
The objective of the research were to know the adoption levels of the conservation technology of dry nad to know the social economic factors which influenced to adoption levels of the conservation technology in Bantul district. The method of collecting the primary data has done with interview, with thw some samples are 60 peoples